Research Progress on the Mechanism of Persistent Low-Level HBsAg Expression in the Serum of Patients with Chronic HBV Infection - Jie Wu; Yu Yu; Yuzhu Dai; Yingjie Zhang; Jun Cheng (Journal of Immunology Research)
Among HBV-infected persons, there is a group of people with hepatitis B surface antigen (HBsAg) showing persistently low levels of expression. The production of low-level HBsAg does not mean a good outcome of chronic HBV infection. Patients still have virus replication and sustained liver damage, and they have the potential to transmit the infection. This risk poses a challenge to clinical diagnosis and blood transfusion safety and is a major concern of experts. However, the mechanism behind persistent low-level HBsAg expression in serum is not completely clear, and complete virus clearance by the host is vital. In this review, we summarize the research progress on the mechanism behind low-level expression of HBsAg in patients with chronic HBV infection in recent years.